Identifying Patterns of Delirium in Hospitalized Patients on Dexamethasone Using a Chart Abstraction Tool. (2nd January 2018) - Chang, Jane T.; Atayee, Rabia S.; Edmonds, Kyle P.
Abstract: Delirium is a neuropsychiatric syndrome that can occur in hospitalized patients, including in palliative care settings. The aim of this study is to describe patterns of delirium in patients receiving dexamethasone at the request of an inpatient palliative consultation team by using a modified chart abstraction tool. This retrospective study analyzed patterns of delirium development in adult hospitalized patients receiving opioids for cancer-related pain and initiated on dexamethasone with recommendation from the palliative care team. Primary end point described patterns of delirium, and the study secondarily analyzed source delirium documentation, Glasgow Coma Scale score, Richmond Agitation-Sedation Scale score, and Eastern Cooperative Oncology Group Performance pre- and post-dexamethasone administration. A total 59 patients were included in this retrospective chart review. There was no difference in delirium rate during the pre- and post-dexamethasone periods ( n = 35 and 31, respectively; P = .62). There also were no significant differences in mental status, agitation, or functional status before or after dexamethasone, although data were limited by electronic health record incompleteness. Evidence of delirium was most commonly documented in physician notes ( n = 58, 71%). The findings showed that incidence and severity of delirium were not impacted after patients were started on dexamethasone as recommended by an inpatient palliative team, although data were limited.